Analisis Spasial dan Pemetaan Zonasi Rawan Bencana Banjir di Kota Gorontalo Berbasis Sistem Informasi Geografis (SIG) - Ramla Hartini Melo; Iswan Dunggio; Rahmat .H. Salote; Rahmat Liputo; Syarifah Fatimah Setiasih Niode (Universitas Negeri Gorontalo, 2025)
This study aims to conduct spatial analysis and mapping of flood hazard zoning in Gorontalo City using a Geographic Information System (GIS). Indonesia, as a “disaster supermarket,” faces floods as the most dominant meteorological and hydrological threat. Gorontalo City has been recorded as highly affected; as of July 2024, 4,686 houses and 41,164 residents were impacted by flooding, with Biawu Subdistrict identified as the most severely affected area. The research method employs spatial analysis of secondary data using overlay techniques on variables including administrative boundaries, soil types, slope gradient, and rainfall, all in shapefile (SHP) format. Data sources are integrated from BNPB’s InaRISK and Google Satellite imagery. The results indicate that the majority of Gorontalo City falls within a high-risk zone (red), concentrated in the lowland central to northern areas encompassing Kota Tengah, Kota Selatan, Kota Timur, Dungingi, and Sipatana Districts. This high level of vulnerability is driven by a combination of flat topography, low soil infiltration capacity, and high rainfall. The resulting map serves as a strategic scientific instrument for the government in formulating adaptive mitigation and spatial planning policies to minimize future disaster risks.